Chemical sustainability issues in manufacturing of 3d printed parts: A state of art review. (2021) - Kumar, Pawan; Kumar, Ranvijay
Abstract: 3D printers are revolutionizing the manufacturing domain as production of high precision, defect less and functional prototypes which fit over mechanical, morphological, tribological, chemical, and thermal aspects.3D manufactured parts are highly appreciable for formation of composite material for use in different engineering applications. A number of studies have been reported by researchers in 3D printing field for better sustainability of the 3D manufactured parts by addition/reinforcement of the metallic/nonmetallic particles. The sustainability in terms of mechanical, morphological, tribological, chemical and thermal aspect ishighly affected by the material issues, machining parameters and manufacturing environment. The present study reviewed the applicability of the 3D printing technology for better sustainability of 3D printed parts over material, fabrication and processing issues.